A family history study of intermittent explosive disorder - Coccaro, Emil F. (Journal of psychiatric research, 2010)
Intermittent Explosive Disorder (IED) is newly appreciated as a commonly occurring disorder of impulsive aggression. Since aggression and impulsivity are under genetic influence, IED may be familial. Blinded and controlled family history study of IED and co-morbid conditions in an outpatient clinical research center for impulsive aggression. The subjects were first-degree relatives of individuals who did and did not meet criteria for IED by DSM-IV and Research Criteria. Elevated Morbid Risk of IED was observed in relatives of IED Probands compared with relatives of Non-IED Probands. This familial signal of IED was not affected by comorbidity in the IED Probands of comorbidity in the relatives of the IED Probands. IED, as defined by research criteria, appears to be familial and may not be an artifact of other co-morbid conditions.